Micron calcium silicate / polyether-ether-ketone composite material and preparation method thereof

By adding calcium silicate in polyether etherone and performing surface treatment, the problem of insufficient biological activity of polyether etherone ketone ketone is solved, prepared composite materials with excellent mechanical properties and cell adhesion rates, and realized biological compatibility The significant improvement of sex and adhesion.

CN119371805AActive Publication Date: 2025-01-28SHANGHAI REACH MEDICAL INSTR

Patent Information

Application Number
CN202411624244.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-01-28
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

The existing polyether ether ketone materials have poor biological activity in biological applications and insufficient osteogenic performance. Common surface spraying methods are prone to cause coating to fall off, and the mechanical properties of the preparation of porous structures are problematic.

Method used

The preparation method of composite materials for calcium silicate and polyether etherone ketone is used to combine the use of surface treatment technology through melting and squeezing granules and injection molding techniques, including the use of modified calcium silicate and porous shells. Overheat crosslinks to improve the biocompatibility and adhesion of composite materials.

Benefits of technology

A composite material with excellent mechanical performance, high cell adhesion rate, and significant osteo biological activity. The layers after surface treatment are closely bonded with the matrix, which is not easy to fall off without affecting surface performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371805A_ABST
    Figure CN119371805A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of polymer composite materials, and particularly discloses a micron calcium silicate / polyether-ether-ketone composite material and a preparation method thereof. The preparation method comprises the following steps: taking polyether-ether-ketone granules, drying, melting, exhausting, adding calcium silicate powder, mixing, vacuumizing, extruding into strips, blow-drying water, cutting into granules, and screening by a vibrating screen to obtain the micron calcium silicate / polyether-ether-ketone composite material. Sulfonating a micron calcium silicate / polyether-ether-ketone composite material, and soaking the micron calcium silicate / polyether-ether-ketone composite material in a dopamine Tris-HCl solution to obtain a PDA modified composite material; taking the modified calcium silicate and the modified porous chitosan, adding the modified calcium silicate and the modified porous chitosan into ethanol, uniformly stirring to obtain a treating fluid, adjusting the pH value, adding a photoinitiator, uniformly stirring, soaking the PDA modified composite material in the treating fluid, treating under ultraviolet light, soaking for 2-3 hours, and drying to obtain the surface-treated micron calcium silicate / polyether-ether-ketone composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer composite materials, and specifically discloses a micron calcium silicate / polyetheretherketone composite material and a preparation method thereof. Background Art

[0002] As people's life expectancy increases and their work and rest habits change, the number of people suffering from spinal diseases is gradually increasing. The commonly used treatment method is spinal interbody fusion, which is to implant a spinal fusion device during surgery. Polyetheretherketone has good biocompatibility, low friction coefficient, good corrosion resistance, and its elastic modulus is close to that of cortical bone. After being implanted into the human body, it will not cause problems such as bone absorption and interface loosening, making it an ideal material for interbody fusion devices.

[0003] However, polyetheretherketone has poor biological activity and poor osteogenic performance, and cannot form bony fusion. This problem needs to be improved urgently. In the prior art, bioactive materials are often sprayed on the surface of polyetheretherketone to improve its osteogenic ability, but this method has the problem of easy detachment of the coating; and the preparation of porous polyetheretherketone has the problem of decreased mechanical properties; in summary, it is of great significance to study a polyetheretherketone-based composite material with good mechanical properties and good biological activity. Summary of the invention

[0004] The object of the present invention is to provide a micron calcium silicate / polyetheretherketone composite material and a preparation method thereof, so as to solve the problems raised in the prior art.

[0005] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a method for preparing a micron calcium silicate / polyetheretherketone composite material, comprising the following steps: taking polyetheretherketone pellets, drying, melting at 370-390°C, exhausting, adding calcium silicate powder, mixing and vacuuming, extruding filaments with a diameter of 1.5-2 mm, drying the moisture, cutting into pellets with a diameter of 2.8-3.5 mm, and screening through a vibrating screen to obtain a micron calcium silicate / polyetheretherketone composite material.

[0006] More optimally, the mass ratio of the polyetheretherketone granules to the calcium silicate powder is (6-7): (3-4).

[0007] More optimally, the preparation of the calcium silicate powder refers to the existing technology, and specifically includes the following steps: taking calcium nitrate tetrahydrate and sodium metasilicate nonahydrate, respectively preparing a calcium nitrate aqueous solution and a sodium metasilicate aqueous solution with a concentration adjusted to 0.5-1 mol / L; adding 0.5-1.5 parts of polyethylene glycol (PEG-600) to 300 parts of the calcium nitrate aqueous solution, and then dripping 300 parts of the sodium metasilicate aqueous solution to generate a precipitate; washing the precipitate with deionized water, adding 200-300 parts of dimethylformamide, heating to evaporate the water while stirring, and then extracting and removing the dimethylformamide, and the obtained product is dried at 50-70°C, and then calcined at a high temperature of 900°C, and after cooling, passed through a 400-mesh sieve to obtain calcium silicate powder.

[0008] More optimally, the micron calcium silicate / polyetheretherketone composite material is subjected to surface treatment to finally obtain a surface-treated micron calcium silicate / polyetheretherketone composite material, which specifically includes the following steps: Step 1: Take the micron calcium silicate / polyetheretherketone composite material, pre-treat it, soak it in a dopamine Tris-HCl solution, control the pH to 8-9, and polymerize it for 20-24 hours to obtain a PDA-modified composite material; Step 2: Soak the porous calcium silicate in a protein solution, add β-mercaptoethanol, stand at room temperature for 12 to 15 hours, filter and dry to obtain modified calcium silicate; Step 3: Take porous chitosan, add acetic acid aqueous solution, stir evenly, add methacrylic anhydride, stir at 40-45°C in dark for 10-12h, wash and dry to obtain modified porous chitosan; Step 4: Take modified calcium silicate and modified porous chitosan, add them to ethanol and stir evenly to obtain a treatment solution, adjust the pH to 8-9, add a photoinitiator, stir evenly, immerse the PDA modified composite material therein, treat under ultraviolet light for 20-30 minutes, soak for 2-3 hours, and dry to obtain a surface-treated micron calcium silicate / polyetheretherketone composite material.

[0009] More optimally, the pretreatment is sulfonation treatment, and the specific process is: take the micron calcium silicate / polyetheretherketone composite material, immerse it in concentrated sulfuric acid with a mass concentration of 98%, stir it for 5-8 minutes, wash and dry it, and obtain the sulfonated composite material.

[0010] More optimally, the concentration of the dopamine Tris-HCl solution is 2-5 mg / mL.

[0011] Preferably, the protein solution contains bovine serum albumin with a concentration of 200-300 mg / ml; and the amount of β-mercaptoethanol added is 200-300 mM.

[0012] More optimally, the method for preparing the protein solution is: taking a TCEP solution, adjusting the pH value to 4-6, and mixing it with a bovine serum albumin solution to obtain a protein solution.

[0013] More optimally, the preparation of the porous calcium silicate refers to the existing technology, and specifically includes the following steps: taking calcium nitrate tetrahydrate and sodium metasilicate nonahydrate, respectively preparing a calcium nitrate aqueous solution and a sodium metasilicate aqueous solution with a concentration adjusted to 0.5-1 mol / L; adding dodecyltrimethylammonium chloride and polyacrylamide to 300 parts of the sodium metasilicate aqueous solution, stirring evenly, to obtain a sodium silicate aqueous solution containing a surfactant; adding 300 parts of the calcium nitrate aqueous solution dropwise to obtain an emulsion, aging at 4-5°C for 20-24h, filtering, washing, and drying at 50-70°C to obtain porous calcium silicate.

[0014] More optimally, the amount of dodecyltrimethylammonium chloride added is 10-15% of the mass of sodium metasilicate nonahydrate; and the amount of polyacrylamide added is 2-4% of the mass of sodium metasilicate nonahydrate.

[0015] More optimally, the modified porous chitosan comprises the following raw materials, calculated by weight: 2-3 parts of porous chitosan and 5-8 parts of methacrylic anhydride.

[0016] More optimally, the preparation of the porous chitosan refers to the prior art, and specifically includes the following steps: adding chitosan to a 2 vol% acetic acid aqueous solution to obtain a chitosan acetic acid aqueous solution with a mass concentration of 2%; Add 3-5 parts of anhydrous calcium chloride to 20 parts of deionized water, add 1-2 parts of PEG-600, and disperse evenly to obtain a calcium chloride solution; At room temperature, 40-50 parts of liquid paraffin and 0.5-1 part of Span-80 are mixed evenly, chitosan acetic acid aqueous solution and calcium chloride solution are added, the temperature is raised to 55-60° C. and stirred for 1-2 hours, 2-3 parts of 25wt% glutaraldehyde aqueous solution are added, the pH is adjusted to 9-10, the temperature is raised to 70-75° C. and reacted for 2-3 hours, acetone is added and ultrasonic demulsification is performed for 5-8 minutes, and after reduced pressure filtration, the product is washed with petroleum ether, ethanol and deionized water in turn and vacuum dried to obtain porous chitosan.

[0017] More optimally, the chitosan Mw=120000 g / mol, and the molar ratio of chitosan to anhydrous calcium chloride is 1:(8~10).

[0018] More optimally, the concentration of the treatment solution is 3-5 mg / mL; the mass ratio of modified calcium silicate to modified porous chitosan in the treatment solution is 1:(3-4).

[0019] More optimally, the amount of photoinitiator used is 0.05% (W / V) of the volume of the treatment liquid.

[0020] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: calcium silicate is added to polyetheretherketone, and calcium silicate has excellent biological activity and biocompatibility. The melt extrusion granulation and injection molding technology are adopted, and the process is optimized and the polyetheretherketone / calcium silicate addition ratio is adjusted (too little calcium silicate addition leads to little improvement in biological activity, and too much calcium silicate addition leads to uneven dispersion and decreased mechanical properties), so that calcium silicate is evenly dispersed in polyetheretherketone, and a composite material with excellent mechanical properties, good cell adhesion rate and excellent bone biological activity is prepared; In order to further improve the surface bioactivity of the composite material, surface treatment was carried out; the treatment solution included modified calcium silicate and modified porous chitosan in a mass ratio of 1: (3~4); wherein the modified calcium silicate was obtained by modifying porous calcium silicate with protein solution and β-mercaptoethanol, and the porous structure was helpful to improve the surface roughness and adhesion, the protein solution contained bovine serum albumin, which could improve the biocompatibility and adhesion, β-mercaptoethanol was a disulfide bond reducing agent, which could make it easier for bovine serum albumin to coat porous calcium silicate, and after reducing the disulfide bonds to thiol groups, it could react with modified porous chitosan containing double bonds in the subsequent steps, and improve the adhesion after cross-linking; the modified porous chitosan was porous chitosan modified with methacrylic anhydride, and chitosan itself had good biocompatibility and antibacterial ability, and after being modified and grafted with double bonds, it could cross-link with modified calcium silicate under ultraviolet light in the subsequent steps, thereby improving the adhesion on the surface of the composite material and making it less likely to fall off; The surface of the composite material is also modified by dopamine self-polymerization, and has good adhesion. The catechol group is oxidized into a quinone structure in an alkaline environment, and reacts with the thiol, amino and other groups in the modified calcium silicate and modified porous chitosan to further enhance the binding force. The treatment liquid contains a photoinitiator, and the modified calcium silicate and modified porous chitosan are cross-linked during ultraviolet treatment to enhance the binding force and adhesion. That is, during the surface treatment, the modified calcium silicate and modified porous chitosan in the treatment liquid are combined with the surface of the composite material in a variety of ways, tightly and not easy to fall off. The concentration of the treatment solution needs to be controlled at 3~5mg / mL. Too high a concentration will cause excessive amounts of modified calcium silicate and modified porous chitosan to fall off easily, which may cause an inflammatory reaction. Excessive porous structures on the surface will also cause the surface to be easily damaged. In summary, the present invention adopts a process of first melt-extruding to obtain a polyetheretherketone / calcium silicate composite material and then surface treating it, which ensures the mechanical properties of the composite material itself and improves its biological activity. At the same time, the layer obtained by the surface treatment is tightly bonded to the matrix and is not easy to fall off, and will not cause a decrease in surface performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a surface SEM photograph of the micron calcium silicate / polyetheretherketone composite material in Example 1; Figure 2 This is a cross-sectional SEM photograph of the micron calcium silicate / polyetheretherketone composite material in Example 1. DETAILED DESCRIPTION

[0022] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] The following parts are by mass unless otherwise specified; Preparation of porous chitosan: chitosan is added to a 2 vol% acetic acid aqueous solution to obtain a chitosan acetic acid aqueous solution with a mass concentration of 2%; 4 parts of anhydrous calcium chloride are added to 20 parts of deionized water, and 1 part of PEG-600 is added, and the mixture is evenly dispersed to obtain a calcium chloride solution; at room temperature, 50 parts of liquid paraffin and 1 part of Span-80 are evenly mixed, and the chitosan acetic acid aqueous solution and the calcium chloride solution are added, the mixture is heated to 55° C. and stirred for 1 hour, 3 parts of a 25 wt% glutaraldehyde aqueous solution are added, the pH is adjusted to 9, the mixture is heated to 70° C. and reacted for 2 hours, acetone is added, and ultrasonic demulsification is performed for 8 minutes, and after vacuum filtration, the product is washed with petroleum ether, ethanol and deionized water in sequence, and vacuum dried to obtain porous chitosan; the chitosan Mw=120000 g / mol, and the molar ratio of chitosan to anhydrous calcium chloride is 1:8; Preparation of calcium silicate powder: Take calcium nitrate tetrahydrate and sodium metasilicate nonahydrate, respectively prepare calcium nitrate aqueous solution and sodium metasilicate aqueous solution adjusted to a concentration of 0.5 mol / L; add 1 part of polyethylene glycol to 300 parts of calcium nitrate aqueous solution, then drop 300 parts of sodium metasilicate aqueous solution to generate a precipitate; wash the precipitate with deionized water, add 300 parts of dimethylformamide, heat and evaporate water under stirring, then extract and remove dimethylformamide, dry the obtained product at 60°C, calcine at 900°C, and pass through a 400-mesh sieve after cooling to obtain calcium silicate powder; Preparation of porous calcium silicate: Take calcium nitrate tetrahydrate and sodium metasilicate nonahydrate, respectively prepare calcium nitrate aqueous solution and sodium metasilicate aqueous solution adjusted to 0.5 mol / L; add dodecyltrimethylammonium chloride and polyacrylamide to 300 parts of sodium metasilicate aqueous solution, stir evenly, and obtain a sodium silicate aqueous solution containing surfactant; drop 300 parts of calcium nitrate aqueous solution to obtain an emulsion, age at 4°C for 20h, filter, wash, and dry at 60°C to obtain porous calcium silicate; the amount of dodecyltrimethylammonium chloride added is 12% of the mass of sodium metasilicate nonahydrate; the amount of polyacrylamide added is 3% of the mass of sodium metasilicate nonahydrate; Preparation of protein solution: Take TCEP solution, adjust the pH value to 5, and mix with bovine serum albumin solution to obtain protein solution; the protein solution contains bovine serum albumin at a concentration of 200 mg / ml; Example 1: Take polyetheretherketone pellets, dry them in a drying machine at 150°C for 4 hours, add them into a twin-screw to melt at 370-390°C, exhaust the air, add calcium silicate powder, add them into the twin-screw to mix, and evacuate; extrude them from a die, quickly cool and harden them into Φ1.8 mm filaments in a water cooler; use an air knife to blow dry the moisture on the filaments; use a pelletizer to cut them into Φ1.8x3.15 mm pellets; use a vibrating screen to screen; obtain a micron calcium silicate / polyetheretherketone composite material; the mass ratio of polyetheretherketone pellets to calcium silicate powder is 7:3.

[0024] Example 2: Take the micron calcium silicate / polyetheretherketone composite material prepared in Example 1 and perform surface treatment: S1: Take the micron calcium silicate / polyetheretherketone composite material, immerse it in concentrated sulfuric acid with a mass concentration of 98%, stir it at 500rpm / min for 5min, take it out and place it in deionized water to terminate the reaction, then wash it in acetone and deionized water for 30min respectively, and dry it at 60°C to obtain a sulfonated composite material; S2: Take the sulfonated composite material, soak it in a 4 mg / mL dopamine Tris-HCl solution, control the pH to 8.5, and polymerize for 24 hours to obtain a PDA-modified composite material; S3: Soak the porous calcium silicate in the protein solution, add 250 mM β-mercaptoethanol, let stand at room temperature for 12 h, filter and dry to obtain modified calcium silicate; S4: Take 3 parts of porous chitosan, add 100 parts of 4% v / v acetic acid aqueous solution, heat at 60°C and stir for 12 hours, add 8 parts of methacrylic anhydride, stir at 40°C in dark for 12 hours, wash and dry to obtain modified porous chitosan; S5: Take modified calcium silicate and modified porous chitosan in a mass ratio of 1:4, add them to ethanol to obtain a treatment solution with a concentration of 4 mg / mL, adjust the pH to 8, add photoinitiator 1173, stir evenly, immerse the PDA-modified composite material therein, treat it under ultraviolet light at 360 nm for 30 minutes, then soak it for 3 hours, and dry it to obtain a surface-treated micron calcium silicate / polyetheretherketone composite material.

[0025] Example 3: The micron calcium silicate / polyetheretherketone composite material prepared in Example 1 was subjected to surface treatment: S1: The micron calcium silicate / polyetheretherketone composite material was immersed in 98% concentrated sulfuric acid, stirred at 500 rpm / min for 5 min, taken out and placed in deionized water to terminate the reaction, then washed in acetone and deionized water for 30 min respectively, and dried at 60° C. to obtain a sulfonated composite material; S2: Take the sulfonated composite material, soak it in a 5 mg / mL dopamine Tris-HCl solution, control the pH to 8.5, and polymerize it for 24 hours to obtain a PDA-modified composite material; S3: soaking porous calcium silicate in a protein solution, adding 200 mM β-mercaptoethanol, standing at room temperature for 12 h, filtering and drying to obtain modified calcium silicate; S4: Take 2 parts of porous chitosan, add 100 parts of 4% v / v acetic acid aqueous solution, heat at 60°C and stir for 12 hours, add 5 parts of methacrylic anhydride, stir at 40°C in dark for 12 hours, wash and dry to obtain modified porous chitosan; S5: Take modified calcium silicate and modified porous chitosan in a mass ratio of 1:3, add them to ethanol to obtain a treatment solution with a concentration of 4 mg / mL, adjust the pH to 8, add photoinitiator 1173, stir evenly, immerse the PDA-modified composite material therein, treat it under ultraviolet light at 360 nm for 30 minutes, soak it for another 3 hours, and dry it to obtain a surface-treated micron calcium silicate / polyetheretherketone composite material.

[0026] Comparative Example 1 (no photoinitiator is added, no ultraviolet light treatment is performed, and the remaining method steps are consistent with Example 2): Take the micron calcium silicate / polyetheretherketone composite material prepared in Example 1 and perform surface treatment: S1: Take the micron calcium silicate / polyetheretherketone composite material, immerse it in concentrated sulfuric acid with a mass concentration of 98%, stir it at 500 rpm / min for 5 minutes, take it out and place it in deionized water to terminate the reaction, then wash it in acetone and deionized water for 30 minutes respectively, and dry it at 60°C to obtain a sulfonated composite material; S2: Take the sulfonated composite material, soak it in a 4 mg / mL dopamine Tris-HCl solution, control the pH to 8.5, and polymerize it for 24 hours to obtain a PDA-modified composite material; S3: Soak the porous calcium silicate in the protein solution, add 250 mM β-mercaptoethanol, let stand at room temperature for 12 h, filter and dry to obtain modified calcium silicate; S4: Take 3 parts of porous chitosan, add 100 parts of 4% v / v acetic acid aqueous solution, heat at 60°C and stir for 12 hours, add 8 parts of methacrylic anhydride, stir at 40°C in dark for 12 hours, wash and dry to obtain modified porous chitosan; S5: Take modified calcium silicate and modified porous chitosan in a mass ratio of 1:4, add them to ethanol to obtain a treatment solution with a concentration of 4 mg / mL, adjust the pH to 8, stir evenly, immerse the PDA modified composite material therein, soak for 3 hours, and dry to obtain a surface-treated micron calcium silicate / polyetheretherketone composite material.

[0027] Comparative Example 2 (replacing the PDA modified composite material with a micron calcium silicate / polyetheretherketone composite material, and the remaining method steps are consistent with Example 2): Take the micron calcium silicate / polyetheretherketone composite material prepared in Example 1 and perform surface treatment: S1: soak the porous calcium silicate in a protein solution, add 250mM β-mercaptoethanol, stand at room temperature for 12h, filter and dry to obtain modified calcium silicate; S2: Take 3 parts of porous chitosan, add 100 parts of 4% v / v acetic acid aqueous solution, heat at 60°C and stir for 12 hours, add 8 parts of methacrylic anhydride, stir at 40°C in dark for 12 hours, wash and dry to obtain modified porous chitosan; S3: Take modified calcium silicate and modified porous chitosan in a mass ratio of 1:4, add to ethanol to obtain a treatment solution with a concentration of 4 mg / mL, adjust the pH to 8, add photoinitiator 1173, stir evenly, immerse the micron calcium silicate / polyetheretherketone composite material therein, treat under ultraviolet light at 360nm for 20-30min, soak for 3h, and dry to obtain a surface-treated micron calcium silicate / polyetheretherketone composite material.

[0028] Comparative Example 3 (increasing the concentration of the treatment solution, and the remaining steps are consistent with Example 2): Take the micron calcium silicate / polyetheretherketone composite material prepared in Example 1 and perform surface treatment: S1: Take the micron calcium silicate / polyetheretherketone composite material, immerse it in concentrated sulfuric acid with a mass concentration of 98%, stir it at 500 rpm / min for 5 minutes, take it out and place it in deionized water to terminate the reaction, then wash it in acetone and deionized water for 30 minutes respectively, and dry it at 60°C to obtain a sulfonated composite material; S2: Take the sulfonated composite material, soak it in a 4 mg / mL dopamine Tris-HCl solution, control the pH to 8.5, and polymerize it for 24 hours to obtain a PDA-modified composite material; S3: Soak the porous calcium silicate in the protein solution, add 250 mM β-mercaptoethanol, let stand at room temperature for 12 h, filter and dry to obtain modified calcium silicate; S4: Take 3 parts of porous chitosan, add 100 parts of 4% v / v acetic acid aqueous solution, heat at 60°C and stir for 12 hours, add 8 parts of methacrylic anhydride, stir at 40°C in dark for 12 hours, wash and dry to obtain modified porous chitosan; S5: Take modified calcium silicate and modified porous chitosan in a mass ratio of 1:4, add them to ethanol to obtain a treatment solution with a concentration of 8 mg / mL, adjust the pH to 8, add photoinitiator 1173, stir evenly, immerse the PDA-modified composite material therein, treat it under ultraviolet light at 360 nm for 30 minutes, then soak it for 3 hours, and dry it to obtain a surface-treated micron calcium silicate / polyetheretherketone composite material.

[0029] Comparative Example 4 (calcium silicate powder is used instead of porous calcium silicate, and the other method steps are consistent with Example 2): Take the micron calcium silicate / polyetheretherketone composite material prepared in Example 1 and perform surface treatment: S1: Take the micron calcium silicate / polyetheretherketone composite material, immerse it in concentrated sulfuric acid with a mass concentration of 98%, stir it at 500 rpm / min for 5 minutes, take it out and place it in deionized water to terminate the reaction, then wash it in acetone and deionized water for 30 minutes respectively, and dry it at 60°C to obtain a sulfonated composite material; S2: Take the sulfonated composite material, soak it in a 4 mg / mL dopamine Tris-HCl solution, control the pH to 8.5, and polymerize for 24 hours to obtain a PDA-modified composite material; S3: Soak the calcium silicate powder in the protein solution, add 250 mM β-mercaptoethanol, stand at room temperature for 12 hours, filter and dry to obtain modified calcium silicate; S4: Take 3 parts of porous chitosan, add 100 parts of 4% v / v acetic acid aqueous solution, heat at 60°C and stir for 12 hours, add 8 parts of methacrylic anhydride, stir at 40°C in dark for 12 hours, wash and dry to obtain modified porous chitosan; S5: Take modified calcium silicate and modified porous chitosan in a mass ratio of 1:4, add them to ethanol to obtain a treatment solution with a concentration of 4 mg / mL, adjust the pH to 8, add photoinitiator 1173, stir evenly, immerse the PDA-modified composite material therein, treat it under ultraviolet light at 360 nm for 30 minutes, then soak it for 3 hours, and dry it to obtain a surface-treated micron calcium silicate / polyetheretherketone composite material.

[0030] In the above examples, the test methods used are conventional methods unless otherwise specified; the raw materials used are commercially available unless otherwise specified, and the sources of the raw materials are as follows: calcium nitrate tetrahydrate (CAS: 13477-34-4); sodium metasilicate nonahydrate (CAS: 13517-24-3); polyethylene glycol (PEG-600, Wuhan Xindadi Environmental Protection Materials Co., Ltd.); dimethylformamide (CAS: 68-12-2); polyetheretherketone granules (KA679524, Jieshikai); acetone (CAS: 67-64-1); dopamine (CAS: 51-61-6); dodecyltrimethylammonium chloride (CAS: 112-00-5); polyacrylamide (S31321, Shanghai Yuanye); chitosan (Mw=120000 g / mol, Shanghai Koraman Reagent Co., Ltd.); acetic acid (CAS: 64-19-7); anhydrous calcium chloride (S24110, Shanghai Yuanye); liquid paraffin (S68179, Shanghai Yuanye); Span-80 (CAS: 1338-43-8); glutaraldehyde (CAS: 111-30-8); petroleum ether (CAS: 8030-30-6); ethanol (CAS: 64-17-5); β-mercaptoethanol (GOY-0957P, Shanghai Guyan); methacrylic anhydride (CAS: 760-93-0); TCEP solution (ZY131056, Zeye Biotechnology); bovine serum albumin solution (H47988, Hubei APT Biotechnology Co., Ltd.); photoinitiator 1173 (CAS: 7473-98-5).

[0031] Experiment: The micron calcium silicate / polyetheretherketone composite material prepared in Example 1 and the surface-treated micron calcium silicate / polyetheretherketone composite materials prepared in Examples 2-3 and Comparative Examples 1-4 were taken; (1) the tensile strength was measured using a universal testing machine with reference to GB / T 1040.1-2018 standard; (2) mouse embryonic osteoblast precursor cells (MC3T3-E1, cell bank of Fudan University, Shanghai, China) were selected for cell experiments; culture: MC3T3-E1 cells were cultured in DMEM medium (Gibco BRL, ThermoFisher Scientific, USA), the culture medium contains 10vol% fetal bovine serum, 100U / mL penicillin, and 100μg / mL streptomycin; the culture medium is placed in a CO2 incubator with 100% humidity, 5% CO2 content, and 37°C; the culture medium is replaced every 3 days; test the cell adhesion rate: the composite material sample is sterilized with ethylene oxide and placed in a sterilized 24-well culture plate; trypsin (0.25%) is added to the culture dish to digest the cells (1 minute), and then cell culture medium is added to stop digestion, centrifuged and the upper culture medium is removed, and cell culture medium is added again and the cells are counted. Then the cells are inoculated on the surface of the material (cell density: 2×10 4cells / well), and the culture plate was placed in a cell culture incubator for 24 hours; then the liquid in the culture plate was removed and the sample was lightly washed with sterile phosphate buffered saline (PBS); finally, the cells remaining on the surface of the material were collected and the number of cells was counted using a CyQUANT® test kit (Life Technologies, Carlsbad, USA); using the same method, the cells were cultured in a culture plate without material samples (TCP), and the number of cells on the well plate after the same culture time was counted as a blank control group; cell adhesion rate (%) = number of cells on the surface of the material / number of cells in the blank control group × 100%; see the table below for specific data; Tensile strength / MPa Cell adhesion rate / % Example 1 92.0 55.6 Example 2 96.6 73.2 Example 3 96.7 73.0 Comparative Example 1 92.6 62.5 Comparative Example 2 92.9 60.4 Comparative Example 3 92.3 69.5 Comparative Example 4 93.2 66.9 Conclusion: In comparative example 1, no photoinitiator is added and no UV treatment is performed. Due to the absence of UV-induced crosslinking, the performance is reduced; in comparative example 2, the PDA-modified composite material is replaced by a micron calcium silicate / polyetheretherketone composite material, and the adhesion is significantly reduced; in comparative example 3, the concentration of the treatment liquid is increased, and the performance is reduced due to the influence of factors such as adhesion. It can be seen that the concentration of the treatment liquid is also of great significance; in comparative example 4, porous calcium silicate is replaced by calcium silicate powder, and the adhesion is reduced due to the reduction of the porous structure; in summary, the micron calcium silicate / polyetheretherketone composite material prepared by the present invention has good mechanical properties and cell adhesion rate, that is, it has good activity.

[0032] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A method for preparing a micron calcium silicate / polyetheretherketone composite material, characterized in that: The following steps are involved: Take polyetheretherketone pellets, dry them, melt them at 370-390°C, exhaust them, add calcium silicate powder, mix them and evacuate them, extrude filaments with a diameter of 1.5-2 mm, blow dry the moisture, cut them into pellets with a diameter of 2.8-3.5 mm, and screen them through a vibrating screen to obtain a micron calcium silicate / polyetheretherketone composite material; The mass ratio of the polyetheretherketone granules to the calcium silicate powder is (6-7): (3-4); The micron calcium silicate / polyetheretherketone composite material is subjected to surface treatment to finally obtain a surface-treated micron calcium silicate / polyetheretherketone composite material, which specifically includes the following steps: Step 1: Take the micron calcium silicate / polyetheretherketone composite material, pre-treat it, soak it in a dopamine Tris-HCl solution, control the pH to 8-9, and polymerize it for 20-24 hours to obtain a PDA-modified composite material; Step 2: Soak the porous calcium silicate in a protein solution, add β-mercaptoethanol, stand at room temperature for 12 to 15 hours, filter and dry to obtain modified calcium silicate; Step 3: Take porous chitosan, add acetic acid aqueous solution, stir evenly, add methacrylic anhydride, stir at 40-45°C in dark for 10-12h, wash and dry to obtain modified porous chitosan; Step 4: Take modified calcium silicate and modified porous chitosan, add them to ethanol and stir evenly to obtain a treatment solution, adjust the pH to 8-9, add a photoinitiator, stir evenly, immerse the PDA modified composite material therein, treat under ultraviolet light for 20-30 minutes, soak for 2-3 hours, and dry to obtain a surface-treated micron calcium silicate / polyetheretherketone composite material; The concentration of the treatment liquid is 3-5 mg / mL; the mass ratio of modified calcium silicate to modified porous chitosan in the treatment liquid is 1:(3-4); The preparation of the porous calcium silicate comprises the following steps: taking calcium nitrate tetrahydrate and sodium metasilicate nonahydrate, respectively preparing a calcium nitrate aqueous solution and a sodium metasilicate aqueous solution with the concentration adjusted to 0.5-1 mol / L; adding dodecyltrimethylammonium chloride and polyacrylamide to 300 parts of the sodium metasilicate aqueous solution, stirring evenly, to obtain a sodium silicate aqueous solution containing a surfactant; dropping 300 parts of the calcium nitrate aqueous solution to obtain an emulsion, aging at 4-5°C for 20-24h, filtering, washing, and drying at 50-70°C, to obtain the porous calcium silicate.

2. The method for preparing a micron calcium silicate / polyetheretherketone composite material according to claim 1, characterized in that: The pretreatment is sulfonation treatment, and the specific process is: taking the micron calcium silicate / polyetheretherketone composite material, immersing it in concentrated sulfuric acid with a mass concentration of 98% and stirring it for 5-8 minutes, washing and drying it to obtain the sulfonated composite material.

3. The method for preparing a micron calcium silicate / polyetheretherketone composite material according to claim 1, characterized in that: The concentration of the dopamine Tris-HCl solution is 2-5 mg / mL.

4. The method for preparing a micron calcium silicate / polyetheretherketone composite material according to claim 1, characterized in that: The protein solution contains bovine serum albumin, the concentration of which is 200-300 mg / ml; and the amount of beta-mercaptoethanol added is 200-300 mM.

5. The method for preparing a micron calcium silicate / polyetheretherketone composite material according to claim 1, characterized in that: The modified porous chitosan comprises the following raw materials, calculated by weight: 2-3 parts of porous chitosan and 5-8 parts of methacrylic anhydride.

6. A micron calcium silicate / polyetheretherketone composite material prepared according to the method for preparing a micron calcium silicate / polyetheretherketone composite material according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Mesoporous calcium magnesium silicate and polyetheretherketone composite, bone prosthesis as well as preparation method and application of composite

    CN104548195A

  • Nano calcium silicate-polyetheretherketone (PEEK) composite material and preparation method thereof

    CN104725771A

  • Porous polyether-ether-ketone-based coating material and preparation method thereof

    CN113304314A

  • Systems and methods for coating bone material

    CN118215450A

  • Tiny Bone Defect Repairing Material, Matrix Material Thereof and Producing Method Thereof

    US20160022864A1

Cited By

  • Reflective heat-insulation energy-saving acrylic plate and preparation method thereof

    CN120209385A